RNA polymerase I mutant affects ribosomal RNA processing and ribosomal DNA stability - Christophe Normand; Christophe Dez; Lise Dauban; Sophie Queille; Sarah Danché; Sarra Abderrahmane; Frederic Beckouet; Olivier Gadal (RNA Biology)
Transcription is a major contributor to genomic instability. The ribosomal RNA (rDNA) gene locus consists of a head-to-tail repeat of the most actively transcribed genes in the genome. RNA polymerase I (RNAPI) is responsible for massive rRNA production, and nascent rRNA is co-transcriptionally assembled with early assembly factors in the yeast nucleolus. In Saccharomyces cerevisiae, a mutant form of RNAPI bearing a fusion of the transcription factor Rrn3 with RNAPI subunit Rpa43 (CARA-RNAPI) has been described previously. Here, we show that the CARA-RNAPI allele results in a novel type of rRNA processing defect, associated with rDNA genomic instability. A fraction of the 35S rRNA produced in CARA-RNAPI mutant escapes processing steps and accumulates. This accumulation is increased in mutants affecting exonucleolytic activities of the exosome complex. CARA-RNAPI is synthetic lethal with monopolin mutants that are known to affect the rDNA condensation. CARA-RNAPI strongly impacts rDNA organization and increases rDNA copy number variation. Reduced rDNA copy number suppresses lethality, suggesting that the chromosome segregation defect is caused by genomic rDNA instability. We conclude that a constitutive association of Rrn3 with transcribing RNAPI results in the accumulation of rRNAs that escape normal processing, impacting rDNA organization and affecting rDNA stability.